2017
DOI: 10.1371/journal.pone.0169941
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Betatrophin Levels and Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThe association between circulating betatrophin levels and gestational diabetes mellitus (GDM) is controversial. The aim of our study was to systematically review available literature linking betatrophin to GDM for a comprehensive understanding of the relationship between circulating betatrophin levels and GDM in human.MethodsPubMed, The Cochrane Library, Medline and CNKI were searched for studies published up to August 2016. Manual searches of references of the relevant original studies were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In adults, ANGPTL8/betatrophin was introduced as an emerging potential player in dyslipidemia with strong association with HDL-Chol and a potential therapeutic tool for the treatment of dyslipidemia [43] . Significantly increased ANGPTL8/betatrophin levels were reported in T2DM with CVDs, T1DM, gestational DM, obesity and MetS [15,[44][45][46][47][48][49] . In an experimental study, ANGPTL8/betatrophin overexpression led to dramatically increased serum TRG levels [50] .…”
Section: Fig 3 Partial Correlation Between Pentraxin-3 and Angiopoiementioning
confidence: 95%
“…In adults, ANGPTL8/betatrophin was introduced as an emerging potential player in dyslipidemia with strong association with HDL-Chol and a potential therapeutic tool for the treatment of dyslipidemia [43] . Significantly increased ANGPTL8/betatrophin levels were reported in T2DM with CVDs, T1DM, gestational DM, obesity and MetS [15,[44][45][46][47][48][49] . In an experimental study, ANGPTL8/betatrophin overexpression led to dramatically increased serum TRG levels [50] .…”
Section: Fig 3 Partial Correlation Between Pentraxin-3 and Angiopoiementioning
confidence: 95%
“…Adipose tissue, recognized as an important endocrine organ, has attracted much attention due to its effect on few metabolic processes such as glucose homeostasis, lipid metabolism, inflammation, and blood pressure. Betatrophin, also known as “ANGPTL8,” “RIFL,” “C19ORF80,” “TD26,” and “lipasin,” is a novel adipokine secreted from the adipose tissue and the liver [3]. Recent studies have indicated that betatrophin is linked to glucolipid disorders [4].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] However, there is still ambiguity as to the levels of betatrophin between GDM and normal pregnant women. A meta-analysis [ 19 ] and a study by Ebert et al [ 20 ] demonstrated that plasma betatrophin levels are higher in GDM patients compared with normal healthy pregnant women. In contrast, Huang et al [ 21 ] reported that betatrophin levels are lower in pregnant GDM women compared with normal healthy pregnant women.…”
Section: Discussionmentioning
confidence: 99%